CFD Modeling for the Influence of Fly Ash Particle Size on the Different Properties of High Concentrated Slurry Transportation in Horizontal Pipe - Baghel, Yatish Kumar; Patel, Vivek Kumar (Trends in Sciences, 2022)
The disposal of fly ash from thermal power plants is becoming a serious concern for environmental engineers. This article attempts to study the influence of particle size of the fly ash on the various properties of high concentrated slurry (50 - 70 % by weight) flow through a horizontal pipe with the help of a commercial CFD code ANSYS FLUENT. Modified Herschel-Bulkley model and SST k-ω turbulence model is used for computational analysis, and the computational outcomes are validated with the available literature. In the present study, the fly ash samples were procured from different coal-based thermal power plants. Various properties: physical and rheological are obtained experimentally. The specific gravity of particles and the static settling concentration (SSC) of the slurry increases with the decrease in the particle size. The rheological properties increase as the concentration increases, and the slurry behaves like a non-Newtonian fluid at a high concentration. In addition, the particle size and concentration intensively impact on the skin friction coefficient and velocity distribution. However, no significant impact on the velocity profile at 70 % concentration (by weight). HIGHLIGHTS The rheological properties increase as the concentration increases, and the slurry behaves like a non-Newtonian fluid at a high concentration CFD modelling of the slurry flow at high concentration with modified Herschel-Bulkley model and SST k-ω turbulence model The particle size and concentration intensively impact on the skin friction coefficient GRAPHICAL ABSTRACT